2021
DOI: 10.1016/j.bios.2020.112686
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic beads combined with carbon black-based screen-printed electrodes for COVID-19: A reliable and miniaturized electrochemical immunosensor for SARS-CoV-2 detection in saliva

Abstract: The diffusion of novel SARS-CoV-2 coronavirus over the world generated COVID-19 pandemic event as reported by World Health Organization on March 2020. The huge issue is the high infectivity and the absence of vaccine and customised drugs allowing for hard management of this outbreak, thus a rapid and on site analysis is a need to contain the spread of COVID-19. Herein, we developed an electrochemical immunoassay for rapid and smart detection of SARS-CoV-2 coronavirus in saliva. The electrochemical assay was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
337
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(348 citation statements)
references
References 36 publications
7
337
2
2
Order By: Relevance
“…Fabiani et al [ 13 ] proposed an electrochemical immunosensor for SARS-CoV-2 detection in saliva. This assay was conceived for the detection of the S1 protein as well as the nucleocapsid protein using magnetic beads (MB) as support (Fig.…”
Section: Electrical and Electrochemical Covid-19 Diagnosis: What Is Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Fabiani et al [ 13 ] proposed an electrochemical immunosensor for SARS-CoV-2 detection in saliva. This assay was conceived for the detection of the S1 protein as well as the nucleocapsid protein using magnetic beads (MB) as support (Fig.…”
Section: Electrical and Electrochemical Covid-19 Diagnosis: What Is Tmentioning
confidence: 99%
“…4 Electrochemical antigenic COVID-19 sensors: a magnetic bead–based electrochemical immunosensors for S1 protein detection: change in DPV signal upon viral binding together with selectivity test (reprinted with permission from ref. [ 13 ]). b Electrochemical biosensors, eCoVSense, using glass slides coated with fluorine-doped tin oxide and modified with Au NPs serving for COVID-19 antibody conjugation by physisorption or electrostatic interactions; the same was performed on screen-printed carbon electrodes where antibodies were immobilized [ 36 ] .…”
Section: Electrical and Electrochemical Covid-19 Diagnosis: What Is Tmentioning
confidence: 99%
“…Although they may present future use as point-of-care diagnostics, further work still needs to be done in order to miniaturize and lower the cost of these biosensors. Currently, optical, electrochemical, and molecularly imprinted biosensors are being designed for the detection of COVID-19 [143][144][145][146][147][148][149], as seen in Table 1:…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 Biosensorsmentioning
confidence: 99%
“…Fig. 3 a Real-time electrochemical biosensing of SARS-CoV-2 RNA [61], b magnetic beadsbased assay for the detection of SARS-CoV-2 in untreated saliva [63], c graphene-based FET biosensor for the detection of SARS-CoV-2 [30] Torrente-Rodriguez studied a multiplexed, portable, wireless graphene-based electrochemical biosensor, which was named the SARS-CoV-2 RapidPlex, for the rapid detection and monitoring of the COVID-19. It was reported that this electrochemical biosensor was able to detect viral antigen nucleocapsid protein, IgM and IgG antibodies, and the inflammatory biomarker C-reactive protein (CRP).…”
Section: Electrochemical Biosensingmentioning
confidence: 99%
“…Fabiani et al [63] investigated a miniaturized electrochemical immunosensor to detect the SARS-CoV-2 virus in saliva (Fig. 3b).…”
Section: Electrochemical Biosensingmentioning
confidence: 99%